Palmyra palm (Borassus aethiopum Mart.) fruits: novel raw materials for the pectin industry. (16th November 2016) - Assoi, Sylvie; Konan, Koffi; Agbo, Georges N; Dodo, Hortense; Holser, Ron; Wicker, Louise
Abstract: BACKGROUND: Preventing post‐harvest waste of Palmyra palm ( Borassus aethiopum Mart.) fruits is possible by recovery of pectin as a value‐added ingredient. Extraction conditions on yield and functionality of Palmyra palm pectin was determined at different temperatures and pH values with 30 min extraction time. RESULTS: Palmyra palm fruits contain more than 650 g kg −1 galacturonic acid and produce soft gels with sucrose in acidic media despite a high degree of acetylation (∼5%). Mechanical deformation of pectin gel was similar when extracted at pH 2.5 and 70 °C or under natural pH at room temperature or 70 °C. Pectins isolated at pH 7 exhibited comparable gel softness ( G ′/ G ″) with commercial pectin. Palm pectins also showed emulsifying activity greater than 50%, attributed to high protein content of 8 g 100 g −1 . For pectins extracted at pH near 5.2–5.5, molar mass ranged from 3.00 to 3.38 × 10 5 g mol −1 ; intrinsic viscosity ranged from 218 to 297 mL g −1 ; arabinose was the main neutral sugar; ζ‐potential ranged from −23 to −25 mV. CONCLUSION: Palm fruit offers an inexpensive raw material to extract pectin in environmentally friendly and economical way and yield a pectin with unique gelling, viscosifying and emulsifying properties. © 2016 Society of Chemical Industry